UPAYA MENGEMBANGKAN MEMBACA PEMULA ANAK MELALUI MEDIA VISUAL WAYANG KERTAS DI PAUD PADA KELOMPOK B - Elis Kurnia; Elia Ratna Dewi (Departement of Mathematics Education, 2019)
All children have the right to take part in early childhood education learning proccess, in Indonesia especially in remote areas early childhood education is very minimal due to a lack of understanding of the community or parents regarding early childhood education. Early childhood education is held to develop the potential of children in six aspects of development, namely cognitive language, social emotional, art, motoric, religious morality. Every child has different potential with other children, so parents and educators need to understand that children's intelligence is not can be judged from the way he/she reads, writes and counts but seen from all aspects of development one of which is the development of language aspects Language development, preschoolers experience rapid development in vocabulary, grammar and syntax according to Piaget, in normal children, language appears to think as concurrent with the form of semiotic reasoning but to stimulate the development of children's language here by using the visual method of Paper Puppets so that children become more interested and easier to understand learning for Paper Puppets have a variety of models so children's language skills can easily be developed.